Plastic catamaran - WANG CHONGGAO (2014)
The utility model discloses a manufacturing technology of a plastic catamaran. The catamaran mainly consists of a left side ship housing (1-1), a right side ship housing (1-2), a ship body left side foam block (2-1), a ship body right side foam block (2-2), a left side ship housing cover plate (3-1), a right side ship housing cover plate (3-2), a ship cabin (4), an outboard motor hanging plate (5), screw holes (6) and nuts (7). The ship body left side foam block (2-1) is put in the left side ship housing (1-1); the ship body right side foam block (2-2) is put in the right side ship housing (1-2); the left side ship housing cover plate (3-1) covers on the left side ship housing (1-1); the right side ship housing cover plate (3-2) covers on the right side ship housing (1-2); and the ship cabin (4) is mounted above the left side ship housing (1-1) and the right side ship housing (1-2), and are connected as a whole by using the bolts. The catamaran has the characteristics of light weight, corrosion resistance, ageing resistance, collision resistance, low ship body stability resistance, low production cost and simple production process.